COMPARATIVE CHARACTERISTICS OF THE UTERUS OF FEMALE WHITE OUTBREED RATS BEFORE AND AFTER LONG-TERM TAKEN OF ENERGY DRINK - Ishankulova Dildora Khabibullaevna (Scholars Digest Publishing, 2024)
This work is devoted to the study of the effect of energy drinks on the histochemical structure of the uterus using the example of female albino rats. The research methods chosen were staining with Schiff's reagent and a positive Schiff (PAS) reaction of the structure of the uterus after long-term use of an energy drink. As a result of the study, it was revealed that there is a proliferation and an increase in the amount of type III collagen. (Reticular fibers) in the uterine tissue of white outbred rats.
Keywords: Schiff (PAS) reaction, Schiff's reagent, histochemical study, uterus, white mixed breed rats, type III collagen.